Compensation for immaterial damage from motor liability in the Republic of Kosovo - Sadiku, Asmir (Technium Social Sciences Journal, 2020)
In the Republic of Kosovo, one of the issues that is mostly encountered in the practice is the compensation for immaterial damage from motor liability. Public transport has multiplied importance for the life and economic development of a country, as this development of various types of public traffic has facilitated the movement of people, and above all the transport of goods and people from one place to another. Contemporary life cannot even be imagined without the different types of public traffic such as: air, road, water and rail transport which include motor vehicles of different types. But, this public traffic needs a normal and safe development. Because, humanity today is paying a huge price with human casualties, risking health, as motor vehicles in addition to becoming pollutants of the human environment, they are also the cause of accidents with great economic damage, bodily injury, and even the loss of life of participants in public traffic. This thesis will address the civil legal liability for damages caused by vehicles in Kosovo, in particular immaterial damage and its compensation, the legal framework that regulates the field of motor liability, cases from court practice, in which the amount of money for compensation of immaterial damage is judged from traffic accidents